Doorkeepers and Gatecrashers: EU Enlargement and Negotiation Strategies - Herbert Brücker; Philipp J. H. Schröder; Christian Weise (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper discusses the eastward enlargement process of the EU in the framework of a simple war of attrition bargaining game. Both players – the existing EU members and the applicants – benefit from enlargement, yet for the applicants reform to the acquis is costly, while the EU prefers substantially reformed candidates. A waiting game unfolds. Within this framework the present enlargement round is analyzed and policy results are deduced. For example, it is shown that delegating the evaluation of applicants to a third party, compensating applicants for their reform efforts or increasing the benefits for new members are all effective negotiation strategies for the EU that have been applied in the process.
Keywords: 330; EU enlargement; eastern enlargement; bargaining; reform; war of attrition; EU-Erweiterung; Verhandlungstheorie; Signalling; Theorie; Osteuropa; war of attrition